Negative equity and housing investment - Andrew Haughwout; Sarah Sutherland; Joseph Tracy (Federal Reserve Bank of New York, 2013)
Housing is a depreciating asset. The rate of depreciation depends on the degree to which households engage in housing investments. Housing investment expenditures economy-wide are sizable, averaging 45 percent of the value of new home construction over the past twenty years. The housing bust and recession coincided with a significant decline in housing investment. Using Consumer Expenditure Survey data from 2007 to 2012, we find that negative equity households reduce their housing investments by roughly 75 percent. The large increase in negative equity due to declining housing prices during the housing bust resulted in a cumulative decline of housing investment expenditures from 2006 to 2010 of 51.2 billion.
Keywords: R31; G21; D13; 330; housing; negative equity